Leukocyte counts and lymphocyte subsets in relation to pregnancy and HIV infection in Malawian women. - Mandala, W; Gondwe, E; Molyneux, M; MacLennan, J; MacLennan, C (Wiley, 2017)
PROBLEM: We investigated leukocyte and lymphocyte subsets in HIV-infected or HIV-uninfected, pregnant or non-pregnant Malawian women to explore whether HIV infection and pregnancy may act synergistically to impair cellular immunity. METHOD OF STUDY: We recruited 54 pregnant and 48 non-pregnant HIV-uninfected women and 24 pregnant and 20 non-pregnant HIV-infected Malawian women. We compared peripheral blood leukocyte and lymphocyte subsets between women in the four groups. RESULTS: Parturient HIV-infected and HIV-uninfected women had more neutrophils (each P<.0001), but fewer lymphocytes (P<.0001; P=.0014) than non-pregnant women. Both groups had fewer total T cells (P<.0001; P=.002) and CD8(+) T cells (P<.0001; P=.014) than non-pregnant women. HIV-uninfected parturient women had fewer CD4(+) and γδ T cells, B and NK cells (each P<.0001) than non-pregnant women. Lymphocyte subset percentages were not affected by pregnancy. CONCLUSION: Malawian women at parturition have an increased total white cell count due to neutrophilia and an HIV-unrelated pan-lymphopenia.